Limits on Higgs boson couplings in Effective field theory. Issue 2 (January 2016) - Belyaev, N; Reid, T
Abstract: We review the Effective Field Theory (EFT) to make projections on physics beyond the Standard Model in the Higgs sector. We provide relations between the non-Standard Model couplings of the Strongly-Interacting Light Higgs (SILH) effective Lagrangian implemented in the eHDecay package and the corresponding terms of the spin-0 Higgs Characterisation model's effective Lagrangian used with the aMC@NLO Monte Carlo generator. Constraints on BSM couplings are determined on the basis of existing experimental limits on Higgs boson width and branching ratios.